Patients' satisfaction with government health care and services in the Taung district, North West Province - MA Bediako; M Nel; LA Hiemstra (AOSIS, 2006)
This was a descriptive study that determined patients' satisfaction with health care in the Taung district state health institutions, North West Province. One hospital, three health centres and five clinics were randomly selected, and consecutive patients were recruited at outpatients during 17 May 2000 - 17 June 2000. The patients completed a questionnaire regarding the service or care provided. Five hundred and sixty seven patients participated in the study. The median age was 30 years, and most patients were female (76.7%). More than half of patients (56.8%) were not satisfied with the availability of medicines and other supplies. Approximately two thirds of patients (65.2%) did not know about the quality of telephone services rendered. There was a high level of dissatisfaction (63.1 %) among patients regarding accessing doctors after hours. Most patients were satisfied with the general attitude of health workers (62.1 %) but 21.2% were dissatisfied. Few (11.7%) patients felt rushed during consultation. Most patients felt they received good health education when their illness was discussed (74.6%). Words and explanations used were easy to understand (76.7%); and they were not discouraged from asking questions (69.9%, n=539). Generally the level of satisfaction among the patients was high except for difficulty in accessing doctors after hours and lack of medicines.